Α‐Aluminiumoxid (α‐Al2O3), Korund (alveolengängige Fraktion) [MAK Value Documentation in German language, 2019]. Issue 2 (25th April 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated α‐aluminium oxide [1344‐28‐1 ]. α‐Aluminium oxide is a biopersistent granular dust. There are no inhalation studies from which a NOAEC could be derived. Therefore, the respirable fraction of α‐aluminium oxide dust is classified in Carcinogen Category 4 and a maximum concentration at the workplace (MAK value) of 0.3 mg/m 3 × material density is established for the respirable fraction by analogy with the other biopersistent granular dusts (GBS). As workers are generally exposed to several aluminium species at the workplace, it is recommended that the biological tolerance value (BAT value) for aluminium is also observed. The classification in Carcinogen Category 4 is based on data that showed increased tumour incidences in rats exposed to biopersistent granular dusts in the high dose range. These tumours are regarded as a consequence of the inflammatory mechanism of action, for which a threshold can be defined. Direct genotoxic effects appear to be of subordinate relevance for the carcinogenicity of biopersistent granular dusts. By analogy with biopersistent granular dusts, Peak Limitation Category II is established for α‐aluminium oxide with an excursion factor of 8. Since α‐aluminium oxide is not systemically distributed and accumulates only locally in the lungs, damage to the embryo or foetus is unlikely when the MAK value or the BAT value is not exceeded. α‐Aluminium oxide is classified accordingly in Pregnancy Risk Group C. α‐Aluminium oxide is not expected to be a sensitizer and is not taken up via the skin in toxicologically relevant amounts.